2021
DOI: 10.3311/ppme.17898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Roughness When Turning and Milling

Abstract: The quality of a machined surface can be described by macro and micro parameters, like the size error, the form and position error or the surface roughness. The task of machining process planning is to find the best machining method and parameters, which ensure the required quality. In this article, the surface roughness in the case of turning and milling technologies is analysed. The effect of the cutting parameters (feed at turning and depth of cut at milling) and the tool parameter (corner radius) are inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Cusp height on constant-Z finishing strategy can be seen in Figure 7, its value can be calculated using the following equation [6]:…”
Section: Figure 7 Cusp Heigh Of Constant-z Startegymentioning
confidence: 99%
“…Cusp height on constant-Z finishing strategy can be seen in Figure 7, its value can be calculated using the following equation [6]:…”
Section: Figure 7 Cusp Heigh Of Constant-z Startegymentioning
confidence: 99%
“…The machining accuracy mainly depends on the extent of the inclination angle, tangential feed, and depth of cut [11] The most used parameters in the quantification of surface quality are the Arithmetic Mean Deviation (Ra) and the Maximum peak to valley height of the profile (Rz). However, it is indicated [12] that these parameters are not always good in the characterization of the machined surface. The results of Yue et al indicated [13] that the original parameters are unsuitable to characterize the textured surfaces, however the Abbot-Firestone curve parameters are more effective for tribological applications.…”
mentioning
confidence: 99%